P018 Understanding Patients' Perceptions of Fecal Microbiota Transplant. (December 2019) - Chauhan, Usha; Popov, Jelena; Kalantar, Mona; Marshall, John; Halder, Smita; Wolfe, Melanie; Moayyedi, Paul; Kaasalainen, Sharon
Abstract : BACKGROUND: Fecal microbiota transplantation (FMT) is becoming popular treatment option for a variety of diseases, including ulcerative colitis (UC). Despite increasing evidence for its role as a therapeutic, currently available literature is limited in its scope to assess firsthand patient experiences. We explored perceptions, attitudes, and experiences of patients who chose to pursue FMT and patients who declined FMT in favor of conventional medications. METHODS: This study used a qualitative descriptive design, embedded within a larger randomized controlled trial (RCT) of adult patients diagnosed with UC enrolled in accessing efficacy of FMT (NCT02606032). Patients were invited to participate in face-to-face semi-structured interviews before and after treatment. Perceptions about FMT were compared to patients who were eligible to participate in the RCT but chose to pursue conventional medications. Interviews were audiotaped, transcribed, and analyzed using thematic analysis. RESULTS: We interviewed 9 patients who underwent FMT treatment and 8 patients who declined FMT treatment. The main themes across the two groups at baseline included: (i) knowledge of FMT, (ii) attitudes around FMT, and (iii) factors contributing to the decision to pursue FMT. Post-FMT, prominent themes included: (i) experiences with FMT, and (ii) perceived response to treatment. We uncovered a poor general understanding of FMT across both cohorts of patients, suggesting a need for improved patient education. Compared to FMT patients, non-FMT patients were less likely to have heard or researched FMT in the past due to feelings of "it just sounds weird". Similar hesitations with FMT were felt across both groups, including fear of transmissible infections, cost of commitment to an experimental therapy, and inherent aversion to stool. Expectations of FMT varied between the two groups, with feelings of hope in the treatment and a sense of "last resort" driving patients to pursue FMT. In contrast, the non-FMT cohort felt a need to further research FMT and explore other treatment options before committing to FMT and were more likely to minimise their disease activity as "not at the severe end". This demonstrates that FMT may be perceived as a "last ditch effort" for many patients. Despite initial aversion, the non-FMT patients demonstrated interest in learning more about FMT and expressed having felt more open to the possibility of pursuing FMT in the future. Those that underwent FMT viewed FMT as a natural treatment and were more eager to explore alternative medicine in comparison to the non-FMT cohort who expressed "I'm not really into the weird stuff". Post-FMT, some patients expressed delight in the perceived change in their symptoms, voicing an improved quality of life, decreased bowel urgency, and less concerns with soiling accidents. CONCLUSION(S): We explored perceptions and experiences with FMT in UC patients who chose to pursue FMT to patients who declined FMT for conventional treatments. While many of the pre-FMT perceptions are comparable across the two groups, important motivating factors in favor of FMT appears to be a perception of naturality and a last resort option. These results suggest that with improved education, FMT may pose an acceptable and tolerable treatment options for patients with UC.